Bacterial productivity in the Prydz Bay and its adjacent waters, Antarctic - 邱雨生; 黄奕普; 陈敏; 刘广山 (国家海洋局极地考察办公室;中国极地研究所, 2004)
Bacterial productivity was measured using 3H-thymidine methods in the Prydz Bay and its adjacent waters in the Southern Ocean during the 16th National Antarctic Research Expedition of China (CHINARE). The results showed that bacterial productivity in our study areas ranged from 4.5 to 191 ngC·dm -3·h -1, with an average of 50.4 ngC·dm -3·h -1. These values were comparable to those reported for the Ross Sea. The mean ratio of bacterial productivity to primary productivity in our study area.